Briquette Making Natural and Synthetic Materials: Pembuatan Briket Bahan Alami dan Bahan Sintesis - Tjahjanti, Prantasi Harmi; Fernanda, Rexy Eca; Ikhsanudin, Achmad Febriyan (Procedia of Social Sciences and Humanities, 2022)
A briquette is a block of combustible material that is used as a fuel to start and maintain a flame. This research makes briquettes made from thermoplastic type plastic bottle waste mixed with natural and synthetic materials. Natural materials using a mixture of coconut fiber, sawdust/wood sawdust with starch adhesive, while the synthetic ones use used cloth or cloth waste, paper waste and Lapindo mud adhesive. The briquette test was carried out, namely the heat test, combustion test, and proximate test. The results obtained that briquettes made from waste/garbage of plastic bottles mixed with natural and synthetic materials can increase the calorific value and combustion value of the briquettes.